Mapping the Landscape of STEM Education in Primary Schools: A Bibliometric Review and Future Outlook - Anggun Ravena Umar; Gema Amades Regina Caeli; Ismahyati Maulidah; Tarmidzi Tarmidzi; Nailah Tresnawati (International Journal of STEM Education for Sustainability, 2026)
Numerous issues exist regarding STEM education in elementary schools. These problems include: 1) ignorance of the need to develop curricula that are in line with elementary school students' cognitive development and comprehension; 2) indifference to the dearth of resources for STEM education, the lack of professional development, and the unequal distribution of STEM education resources, particularly in rural and developing nations. The author used the Scopus.com database to conduct a bibliometric study of primary school STEM education-focused articles in order to comprehend the current state of affairs about STEM education in elementary schools. The author used RStudio to analyze 203 of the papers, and a descriptive analytic approach was used to interpret the analysis's findings. The study's findings show that the quantity of publications devoted to the application of STEM in primary education has significantly increased over time. The number of publications devoted to the use of STEM teaching models at the primary school level shows this trend. The degree of development and STEM education literacy at the primary school level is influenced by the curricular policies, the technology resources available, and the instructors' readiness. More research should concentrate on a comprehensive and more integrated strategy with an emphasis on technological and pedagogical advancements in curriculum creation that is pertinent and aligned with 21st Century educational abilities if it is to have a meaningful and relevant impact.